Internationalization of Higher Education: Potential Benefits and Costs - Tahira Jibeen; Masha Asad Khan (Institute of Advanced Engineering and Science, 2015)
AbstractInternationalization of higher education is the top stage of international relations among universities and it is no longer regarded as a goal in itself, but as a means to improve the quality of education. The knowledge translation and acquisition, mobilization of talent in support of global research and enchantment of the curriculum with international content are considered to be the benefits of internationalization of higher education. Though, internationalization holds many positives to higher education, there are grave risks associated with this multifaceted and growing phenomenon. Negative aspects include commercial profit, academic colonization and difficulty in ensuring quality education. The current review has implications for educational policy makers to ensure positive and reciprocal benefits to the higher education institutions and the countries concerned.